2021
DOI: 10.1002/hyp.14260
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐sensor evaluation of precipitation uncertainty for landslide‐triggering storm events

Abstract: Extreme precipitation can have profound consequences for communities, resulting in natural hazards such as rainfall-triggered landslides that cause casualties and extensive property damage. A key challenge to understanding and predicting rainfall-triggered landslides comes from observational uncertainties in the depth and intensity of precipitation preceding the event. Practitioners and researchers must select from a wide range of precipitation products, often with little guidance. Here we evaluate the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…A correct design of the modelling study should consider a proper selection of the input (precipitation) products for hydrological models because the model parameters and modelling uncertainty will largely depend on this forcing product. Based on papers from this issue, it could be recommended to either test different products to choose the most appropriate one for the purpose of the study (Culler et al, 2021), or to use an ensemble of input forcings instead of using only a single product (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A correct design of the modelling study should consider a proper selection of the input (precipitation) products for hydrological models because the model parameters and modelling uncertainty will largely depend on this forcing product. Based on papers from this issue, it could be recommended to either test different products to choose the most appropriate one for the purpose of the study (Culler et al, 2021), or to use an ensemble of input forcings instead of using only a single product (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In our special issue, all three papers dealing with input uncertainty similarly focus largely on precipitation uncertainty. The papers investigate input (precipitation) uncertainty and its impact on parameter identification in hydrological models (Liu et al, 2021), input uncertainty in observed and generated variables for hydrological models and process representation (Beven, 2021b), and precipitation uncertainty impact on the rainfall‐triggered landslide events (Culler et al, 2021). Beven (2021b) also discusses uncertainties in other input variables, that is, temperature and evapotranspiration.…”
Section: Impact Of Observational Uncertainty On Process Representatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in the prediction of slopes, most scholars focus on the prediction of slope deformation and stability [11][12][13][14][15], and there are few studies on the prediction of landslide damage depth [16]. Landslide damage depth is affected by a variety of factors [17], its uncertainty is higher, and it is more difficult to predict directly. Some scholars believe that shallow landslides parallel to the surface of soil slopes often occur (failure at wet fronts) [18,19]; thus, the range of landslide damage depths can be indirectly determined from rainfall infiltration depths and the prediction of slope infiltration depths is better implementable.…”
Section: Introductionmentioning
confidence: 99%